Association between indicators of dementia and nutritional status in institutionalised older people - Galesi, Lilian Fernanda; Leandro-Merhi, Vânia Aparecida; de Oliveira, Maria Rita Marques [UNESP] (Wiley, 2013)
Background and aims. Dementia weakens older people and can lead to malnutrition; therefore, the objective of this study was to assess the association between indicators of dementia and biochemical indicators, anthropometric indicators and food intake in institutionalised older people. Methods. A total of 150 older people of both genders participated in this study. Nutritional status was determined by body mass index and other anthropometric variables, and biochemical indicators were used to analyse the differences between individuals with and without dementia. Energy and nutrient intakes were determined by food records, and dementia was investigated with the Mini-Mental State Examination. The data were analysed by the chi-square test, Student's t-test and Mann-Whitney tests. Results. Of the 150 individuals studied, 48% were men with a mean age of 73±10years and 52% were women with a mean age of 80±9years. Thirty-six per cent had some degree of malnutrition and 48% presented dementia, which was more prevalent in women (59%). The nutritional status of men and women individuals with and without dementia differed significantly (P<0.001 for men and women). The only variables that presented a significant difference between individuals with and without dementia were those associated with muscle mass in men. There were no differences in energy and nutrient intakes between individuals with and without dementia except for vitamin C intake, which differed among women (P=0.032). Conclusion. In the conditions of the present study, dementia was associated with nutritional status, but not with energy and nutrient intakes, suggesting that older people with dementia may have higher nutritional requirements. Implications for practice. Investigation of dementia may contribute to the nutritional status assessment of older people and energy expenditure and immobility should be investigated for a more complete assessment. © 2012 Blackwell Publishing Ltd.
Keywords: Dementia; Nutritional status; Older people